Buddhist pedagogy in teacher education: cultivating wisdom by skillful means. Issue 2 (15th March 2018) - Ma Rhea, Zane
ABSTRACT: This paper draws on research I have conducted about the cultivation of wisdom in Thailand and Australia. I examine the ancient pedagogy of pavīṇaupāya skillful means investigating how this pedagogy can inform contemporary development of teacher educators and teachers. I examine the Panjaawítee Wisdom Method that has its foundations in the Buddhist Aṭṭhangika-Magga Eightfold Path. Teaching people to walk this path, the pedagogical pavīṇaupāya skillful means described in the Buddhist texts (Various, 2005) has traditionally been underpinned by siinsamaadipanjaa, a series of practices designed to guide the learner to both develop and find balance between morality, concentration, and insight understanding leading to the cultivation of wisdom. I critically discuss the concept of pavīṇaupāya skillful means as the key pedagogical skill needed by the teacher educator and teacher in order to know how to develop this balance and thereby create the causes and conditions for wisdom to emerge in their students.